2013
DOI: 10.1111/psyp.12057
|View full text |Cite
|
Sign up to set email alerts
|

Follow your breath: Respiratory interoceptive accuracy in experienced meditators

Abstract: Attention to internal bodily sensations is a core feature of mindfulness meditation. Previous studies have not detected differences in interoceptive accuracy between meditators and nonmeditators on heartbeat detection and perception tasks. We compared differences in respiratory interoceptive accuracy between meditators and nonmeditators in the ability to detect and discriminate respiratory resistive loads and sustain accurate perception of respiratory tidal volume during nondistracted and distracted conditions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
92
1
6

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(104 citation statements)
references
References 86 publications
(103 reference statements)
5
92
1
6
Order By: Relevance
“…In line with our findings here, effect sizes for changes on this aspect observed in previous studies have been modest. This holds for studies using subjective measures (e.g., Impett et al, 2006) as well as studies using objective measures such as breathing sensitivity (e.g., Daubenmier et al, 2013). We do, however, find significant moderate to large changes (Cohen's d = 0.40 to 0.72) for the IA sub-components of "Self-Regulation," "Attention Regulation," and"Body Listening."…”
Section: Discussioncontrasting
confidence: 46%
“…In line with our findings here, effect sizes for changes on this aspect observed in previous studies have been modest. This holds for studies using subjective measures (e.g., Impett et al, 2006) as well as studies using objective measures such as breathing sensitivity (e.g., Daubenmier et al, 2013). We do, however, find significant moderate to large changes (Cohen's d = 0.40 to 0.72) for the IA sub-components of "Self-Regulation," "Attention Regulation," and"Body Listening."…”
Section: Discussioncontrasting
confidence: 46%
“…In terms of predictive coding, this latter observation is interesting because there is much greater capacity for volitional control of breathing when compared with cardiac regulation. Meditative practices, such as mindfulness, potentially enhance respiratory accuracy [21], while meditation-based therapies reduce anxiety [79]. In addition, physical exercise has been used to treat anxiety disorders [80].…”
Section: (C) Dissociated Dimensions Of Interoception: Clinical Implicmentioning
confidence: 99%
“…tests that are independent of how good or bad the person thinks they are at estimating their interoceptive signals) [97,98]. Attempts at identifying groups of people who might be specifically interoceptively aware have largely proved unsuccessful [96,99,100]. Notably, however, artists such as musicians and dancers have been found to have an enhanced objective awareness of their interoceptive states [101,102], suggesting an interesting route to heightened interoceptive awareness through the arts.…”
Section: The Arts Hypothesismentioning
confidence: 99%
“…It has been suggested that activities that might engage the insular and somatosensory systems could help to reverse the adverse effects of addictions (insula hypo-activation), by enabling access to the frontal control networks of the brain (I-system supporting meaning and awareness of long-term implications, through the insula) [96]. Two pathways provide the rspb.royalsocietypublishing.org Proc.…”
Section: Meaningful Activities: Triggering a 'Me Factor'mentioning
confidence: 99%